2019
DOI: 10.26434/chemrxiv.8006789.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZIF-8 Degrades in Cell Media, Serum, and Some—But Not All—Common Laboratory Buffers

Abstract: <p>The emergence of drug delivery using water stable metal-organic frameworks has elicited a lot of interest in their biocompatibility. However, few studies have been conducted on their stability in common buffers, cell media, and blood proteins. For these studies, single crystal ZIF-8 approximately 1 um in diameter were synthesized, incubated with common laboratory buffers, cell media, and serum, and then characterized by PXRD, IR, DLS, and SEM. Time-resolved SEM and PXRD demonstrate that buffers contai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, as recently reported, ZIF-8 are not stable in several physiological buffers despite the pH being higher than 7. 28,29 This is due to the presence of anions in the buffer such as phosphates, which compete with imidazolates to coordinate the Zn 2+ ions, removing the metal centers from the MOF and causing the structure to break up. The same phenomenon may happen in organic solvents during a core-shell synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, as recently reported, ZIF-8 are not stable in several physiological buffers despite the pH being higher than 7. 28,29 This is due to the presence of anions in the buffer such as phosphates, which compete with imidazolates to coordinate the Zn 2+ ions, removing the metal centers from the MOF and causing the structure to break up. The same phenomenon may happen in organic solvents during a core-shell synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…with the aid of XRD, FTIR, time‐resolved atomic force microscopy (AFM), in situ small angle X‐ray scattering (SAXS) and 31 P NMR. Luzuriaga et al 55 . also reported that treatment with phosphate buffer led to a change in the morphology and composition of ZIF‐8 crystals, although they did not observe a leakage of the green fluorescent protein (GFP) which had been biomimetically mineralized within ZIF‐8.…”
Section: Resultsmentioning
confidence: 99%
“…The latter was demonstrated by Velásquez-Hernández et al 54 with the aid of XRD, FTIR, time-resolved atomic force microscopy (AFM), in situ small angle X-ray scattering (SAXS) and 31 P NMR. Luzuriaga et al 55 also reported that treatment with phosphate buffer led to a change in the morphology and composition of ZIF-8 crystals, although they did not observe a leakage of the green fluorescent protein (GFP) which had been biomimetically mineralized within ZIF-8. Nevertheless, entrapment of tyrosinase@ZIF-8 into alginate gel offers a great solution for improving its robustness and operability.…”
Section: Synthesis Of 3 0 -Hydroxypterostilbene From Pterostilbenementioning
confidence: 99%
“…Nevertheless, even these types of more robust MOFs, such as the widely studied ZIF-8, present a limited stability in buffer media. Despite ZIF-8 being generally unstable in buffer media, with the initial crystalline framework being transformed into other different materials, or even dissolved in the presence of EDTA, ZIF-8 showed stability in the presence of certain buffers [65,66]. Methodologies to precisely monitor MOF stability in the development of analytical applications would be desirable.…”
Section: Future Perspectivesmentioning
confidence: 99%